Determinants of gingival recessions in Portuguese adults - Lapa, João (2021)
Objectives: The objective of this study consisted in determining the prevalence of gingival recession and potential risk factors associated in a sample of patients that had a dental appointment in the University Clinic of the Portuguese Catholic University in Viseu, Portugal. Methods: We conducted an epidemiological observational cross-sectional study where a sample of 101 patients was assessed. The participants were subjected to a questionnaire and an intra-oral clinical examination was made in order to assess gingival recessions. Results: The prevalence of recession was 85.1%. The presence of habits and a high plaque index are associated with the onset of recessions and its severity. The aesthetic condition was influenced only in 14.0% of the cases and just 17.4% of the patients with gingival recession had tooth hipersensibility. There is a stronger association between the development of recessions and using a brushing technique based mostly on horizontal movements and brushes with harder bristles. Conclusion: Although further studies need to be applied in a more representative sample, we conclude that the majority of the analyzed sample has already suitable oral health behaviors, however, some need to be modified as the understanding of the need to change certain habits to prevent development of recessions.